FROM PURPOSE TO PRACTICE: SPIRITUALITY AND MENTAL WELL-BEING IN PHYSIOTHERAPY UNDERGRADUATE COURSES (CIPEEX, 2026)
BACKGROUND: Spirituality is understood as the search for meaning and purpose in life, which may or may not involve religion, and has been associated with the promotion of well-being. Health students, particularly those in Physical Therapy, face emotional, academic, and socioeconomic burdens that make them vulnerable to mental disorders. In this context, spirituality may serve as a coping resource. OBJECTIVE: To interpret the academic reality of Physical Therapy students at UniEVANGÉLICA – Anápolis regarding mental health and to analyze the influence of spirituality in this setting. METHODS: A descriptive, cross-sectional, and quantitative study was conducted with a sample of 43 Physical Therapy students from the 1st, 4th, and 8th semesters. Validated scales were applied through Google Forms. Statistical analysis was performed using SPSS, with significance set at p
Keywords: Physical Therapy Specialty; Physical Therapy Specialty; Spirituality; Spirituality; Mental Health; Mental Health